Tunable multiwavelength brillouin erbium fiber laser designs for high capacity optical communication system - Al-Alimi, Abdulmoghni Ali Waza'a (2014)
This work presents the design and development of a single laser source for multiple wavelengths generation in C-band transmission window to meet the demand from optical communication systems for high transmission rate. The single laser source consists of Brillouin and erbium doped fiber (EDF) gain mediums. The combination of stimulated Brillouin scattering (SBS) effect and EDF gain medium in the same laser cavity forms Brillouin erbium fiber laser (BEFL). The effect of SBS inside an optical fiber is used to initialize Stokes lines and the EDF gain medium is used to compensate the cavity loss as well as to enhance the BEFL performance. Based on the Brillouin-erbium combination, four novel laser configurations have been designed, namely BEFL with nonlinear fiber loop mirror (NOLM), with single pass amplified Brillouin pump (BP) power, with double pass post-amplified BP power and with virtual mirror. These configurations were developed to overcome substantial limitations in the existing BEFL system. One of the limitations of the conventional BEFL is the requirement for high threshold power to generate the first Stokes line and the requirement of high EDF pump power to generate a large number of Stokes lines. Therefore, it is a huge challenge to design a BEFL cavity to reduce these requirements. To address this problem, the author proposed the first system that is BEFL with NOLM. A low threshold power was achieved by utilizing the high reflectivity feature of NOLM. The developed BEFL with NOLM exhibited a low threshold power ranging from 2 mW to 3 mW and 26 stable Stokes lines with wavelength spacing of 0.089 nm (10.5 GHz), which were obtained at low EDF pump power of 25 mW. The second limitation of BEFL is the standard single mode fiber (SSMF) distance requirement for several kilometers or even longer to improve the number of Stokes lines generation. In this work, two new linear cavity BEFL configurations with amplified BP power techniques were successfully designed to enhance the number of Stokes lines in a short length of SSMF. In these configurations, the BP power is amplified once and twice in the EDF gain medium before inserting the Brillouin gain. The second and third configurations are based on single pass (SP) pre-amplified and double pass (DP) post-amplified BP power, respectively. Both BEFL based on SP and DP techniques have improved the number of Stokes lines generation inside the short length of SSMF. Up to 33 and 42 Stokes lines were generated inside SSMF length of 600 m by utilizing SP and DP techniques, respectively. Also, these techniques are able to suppress the built-up of the self lasing over a wide range. The main disadvantage of the conventional BEFL is the existence of self lasing cavity modes together with the generated Stokes lines as the Brillouin wavelength tuned away from the EDF peak gain. This undesirable self lasing limits the tuning range of the BEFL and number of Stokes lines as well. The fourth BEFL design is proposed with the concept of virtual mirror to eliminate the self lasing over a wide tuning range, which resulted in the improvement in the BEFL tuning range. Also, the new design improves the number of Stokes lines by inducing four wave mixing (FWM) inside the Brillouin gain medium. In this new BEFL configuration, the virtual mirror was utilized to prevent the self lasing cavity modes from circulating inside the cavity. Therefore, the generated Stokes lines were tuned throughout the whole C-band from 1532.2 nm to 1572.2 nm with the average number of 100 Stokes lines. Up to 160 channels can be tuned over a tuning range of 26 nm from 1539 nm to 1565 nm. The generated Stokes lines of this BEFL have wavelength spacing of 0.076 nm and individual peak powers of greater than -8 dBm for the first nine Stokes lines. In addition, this BEFL design overcomes the requirement of BP power adjustment in conjunction with the adjustment of the EDF pump power in the linear cavity. As a result, the tunability of the generated Stokes lines is limited only by amplification bandwidth of linear gain medium. Different design parameters such as EDF pump power, BP power, BP wavelength and SSMF length were used to characterize and optimize the four BEFL systems. The effects of these design parameters on the BEFL system performance such as threshold power, number of Stokes lines, total output power, self lasing cavity modes, stability and tuning range, have been analyzed and discussed.